MEMBANGUN KESADARAN PEMILIH RASIONAL MELALUI PENDIDIKAN POLITIK PADA PILKADA 2024 DI KAMPUNG KULUAKMA - Siti Khikmatul Rizqi; Malika Mahdania (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Political education is an important strategy in improving the quality of democracy, especially in the context of regional head elections. This study aims to explore the implementation of a political education program in Kuluakma Village, Walelagama District, Jayawijaya Regency, involving 26 participants from various community backgrounds. The program was designed to raise awareness of rational voting, reduce the influence of money politics, and increase public understanding of the importance of choosing candidates based on competence and work programs. Through a participatory method involving training, group discussions, and electoral simulations, the results of the study show an increase in participants' awareness and understanding of rational voting. Despite challenges related to limited access to information and the influence of local culture, this program is expected to serve as a model that can be adopted in other regions with similar conditions. The recommendations from this study include improving access to information, integrating local cultural values, and providing follow-up training for the community.